Research on precise ammonia injection technology in thermal power plant. Issue 1 (May 2021) - Tu, Anqi; Zhu, Yujie
Abstract: Under the situation of ultra-low emission in China, SCR denitration system generally has the problem of high ammonia escape from the reactor outlet, and the escape ammonia reacts with SO3 in flue gas to generate NH4 HSO4, which will aggravate the blockage of air preheater and affect the denitration efficiency, so the ammonia injection has a great impact on the NOx emission concentration of power plant. In this paper, how to accurately spray ammonia in SCR denitration system is introduced in detail, that is, after the flow field partition optimization of denitration system, the corresponding advanced measurement system, advanced control system and actuator are added combined with the partition.